1998
DOI: 10.1136/fn.79.1.f61
|View full text |Cite
|
Sign up to set email alerts
|

Nasal high frequency ventilation in neonates with moderate respiratory insufficiency

Abstract: Aim-To investigate the eYcacy of nasal high frequency ventilation (nHFV) in newborn infants with moderate respiratory insuYciency. Method-Twenty one preterm and term neonates were treated with nHFV for respiratory insuYciency. Criteria for starting nHFV were: deterioration on nasal CPAP expressed by a median pH of 7.24 and pCO 2 of 8.3 kPa, or increasing FIO 2 . nHFV was delivered using the Infant Star ventilator. Ventilator setting amplitude was 35 cm H 2 O; mean airway pressure 7 cm H 2 O; and frequency 10 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 21 publications
4
62
2
2
Order By: Relevance
“…Short-term observational studies have suggested initial mean airway pressure set to equal the previous CPAP, frequency set at 10 Hz, amplitude adjusted to obtain visible chest-wall vibration and increased every 30 min by 4 -6 units, if necessary, to maintain clinically appropriate chest-wall vibration, transcutaneous CO 2 , or blood gas values. 80,81 Clinical responses to HFV in preterm neonates in 2 small studies have been reported. Van der Hoeven et al 79 placed 21 preterm and term infants with moderate respiratory insufficiency on nasal HFV following CPAP.…”
Section: Nasal High-frequency Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term observational studies have suggested initial mean airway pressure set to equal the previous CPAP, frequency set at 10 Hz, amplitude adjusted to obtain visible chest-wall vibration and increased every 30 min by 4 -6 units, if necessary, to maintain clinically appropriate chest-wall vibration, transcutaneous CO 2 , or blood gas values. 80,81 Clinical responses to HFV in preterm neonates in 2 small studies have been reported. Van der Hoeven et al 79 placed 21 preterm and term infants with moderate respiratory insufficiency on nasal HFV following CPAP.…”
Section: Nasal High-frequency Ventilationmentioning
confidence: 99%
“…All 14 subjects were very-low-birth-weight infants (Ͻ 1,500 g) who were transitioned from CPAP to HFV via nasopharyngeal ETT, with the Infant Star ventilator in the high-frequency, flow-interrupter mode. The investigators used an approach similar to that of van der Hoeven et al, 80 for 2 hours. After 2 hours of nasal HFV, capillary blood gases were measured and the subjects were returned to their pre-study CPAP settings.…”
Section: Nasal High-frequency Ventilationmentioning
confidence: 99%
“…However, beyond 3 to 4 hours of continuous bubble nasal CPAP, Pa CO 2 rose and pH fell to unphysiologic levels, despite treating the preterm lambs with antenatal corticosteroids to accelerate lung development, exogenous surfactant to increase lung compliance, and caffeine citrate to increase respiratory drive. The only prior use of HFNV we are aware of is a small observational study in preterm neonates failing nasal CPAP reported by van der Hoeven and colleagues (28). They applied HFNV with the Infant Star 950 ventilator via a single nasopharyngeal tube in a study group that was quite diverse with respect to gestational and postnatal age.…”
Section: Methods Surgical Preparation and Management Of Preterm Lambsmentioning
confidence: 99%
“…Its use also does not require synchronization of breaths as the patient can comfortably continue normal tidal breathing while on the ventilator and thus has the potential to provide superior noninvasive ventilation. Only a limited number of clinical studies have explored the use of noninvasive high-frequency ventilation but whether this strategy is able to support adequate gas exchange in neonates has not been thoroughly addressed [11,12,13]. …”
Section: Introductionmentioning
confidence: 99%